1997
DOI: 10.1074/jbc.272.47.29566
|View full text |Cite
|
Sign up to set email alerts
|

Alanine Insertion Scanning Mutagenesis of Lactose Permease Transmembrane Helices

Abstract: A priori, single residue insertions into transmembrane helices are expected to be highly disruptive to protein structure and function. We have carried out a systematic analysis of the phenotypes associated with Ala insertions into transmembrane helices in lactose permease, a multispanning Escherichia coli inner membrane protein. Insertion of alanine into the center of 7 transmembrane helices was found to abolish stable integration of lactose permease into the membrane or uphill lactose transport. A more detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 37 publications
(40 reference statements)
2
40
0
Order By: Relevance
“…1A). Alanine insertion into an ␣ helix is believed to dislocate the N-terminal part of the helix by 100°with respect to the C-terminal part and consequently impede the structural and/or functional continuity of the helix (16). Tryptophan scanning has been used successfully to determine functionally important amino acids in integral membrane proteins (16 -18).…”
Section: Expression and Processing Of Fxyd7 Tm Mutants-mentioning
confidence: 99%
“…1A). Alanine insertion into an ␣ helix is believed to dislocate the N-terminal part of the helix by 100°with respect to the C-terminal part and consequently impede the structural and/or functional continuity of the helix (16). Tryptophan scanning has been used successfully to determine functionally important amino acids in integral membrane proteins (16 -18).…”
Section: Expression and Processing Of Fxyd7 Tm Mutants-mentioning
confidence: 99%
“…It has been observed that inserting single amino acids near the central core of transmembrane helices in lactose permease disrupts protein function (30). Three mutants were constructed with an alanine inserted in different hydrophobic sections between loop f and Ser-788.…”
Section: Topology Of the Namentioning
confidence: 99%
“…However, in dealing with disease mutants, multiple amino acid properties are changed, possibly altering function by way of what was introduced, rather than what was taken out. Systematic mutation to a relatively neutral amino acid like alanine (Braun et al 1997) or cysteine, as done in the SCAM studies, is a more interpretable approach, particularly if the overall distribution of sensitive sites on the helices are considered as an indicator of transmembrane domain interactions. Thus, the distribution of cysteine substitutions in the SCAM analysis of Skerrett et al (2002) and Toloue (2007) that led to nonfunctional gap junctions or channels with aberrant properties may provide the strongest indication yet as to the likely sites of interhelical interaction within the connexin.…”
Section: Introductionmentioning
confidence: 99%